Translation Methods in Political Speeches: A Case Study of English Translation of President Joko Widodo’s Inaugural Address - Pamungkas, Muhammad Ersan (Paradigma: Jurnal Kajian Budaya, 2020)
Translating political speeches poses its own challenges and difficulties, with one of the reasons being the fact that political speeches have their own unique features. Translation of political speech is also arguably still underresearched in translation studies. It is for this reason that this paper seeks to investigate translation method(s) that can be used to translate political speeches. The data source of this paper is the English translation of an inaugural address of President Joko “Jokowi” Widodo produced by a professional Australian translator. The speech was translated from Indonesian as the source language (SL) to English as the target language (TL). Appropriate translation methods are obviously needed to produce a higher quality political speech translation. This research applies the concept of translation methods proposed by Newmark (1988). This is a qualitative research with a comparative conceptual method. Results show that the translation methods adopted when translating the inaugural address are semantic and communicative translation methods. Semantic translation method is the most dominant one, followed by communicative translation method. Semantic translation method was used to translate the body part of the speech, while communicative translation method was used to translate the opening part and the closing part of the speech. These two methods are considered appropriate for translating this political speech.